Avaliação da aplicação da espécie Bacillus subtilis no tratamento de meio sintético com alta carga nitrogenada - Machado, Paula Thainá Rodrigues (2021)
The presence of nitrogen in the atmosphere is essential for life, however, the discharge of effluents containing large amounts of nitrogen into receiving bodies can cause damage such as eutrophication, a decrease in the concentration of Dissolved Oxygen (DO) and toxicity. Thus, it becomes necessary to properly control and treat liquid waste so that it complies with the legislation and does not harm the environment. Currently, processes such as denitrification, which consists of the biological reduction of nitrate by converting it into molecular nitrogen, have been presented as a viable alternative both in terms of economics and in terms of employability. In this sense, this work aims to evaluate the ability to reduce the nitrogen load present in synthetic media by using denitrifying bacteria of the Bacillus subtilis species. As well as analyzing a real industrial effluent, in order to verify disposal parameters such as nitrogen load, identifying it as a potential application of the method. The methodology used in this study is based on monitoring the bacteria under their optimal development conditions, evaluating growth, as well as pH, optical density, ammonia and nitrate concentration parameters. With this study, it was possible to identify the capacity of Bacillus subtilis to reduce the nitrogen load present in the synthetic medium, demonstrating the possibility of using the technique in the treatment of industrial effluents. Likewise, industrial effluent was shown to be a potential candidate for the use of this methodology.